Training for the Development of Traditional Educational Game Tools in Increasing the Professional Competence of Teachers - Hifza; Sera Yuliantini; Asyruni Multahada; Astaman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study aimed to investigate the impact of a training program on the professional competence of Pendidikan Anak Usia Dini (PAUD) teachers in developing traditional educational game tools. The training activities employed the experiential learning model, focusing on the steps of traditional APE (Anak Usia Dini Pendidikan, or Early Childhood Education) development: selecting traditional games, choosing materials, adapting games into APE, determining learning themes, and piloting APE with peers. The findings revealed several implications of the training program on the professional competence of PAUD teachers. First, there was a significant increase in teacher knowledge, particularly in traditional APE. Second, teachers became more aware of the importance of traditional APE in early childhood education. Third, teachers' understanding of professional competence was enhanced through the training, enabling them to incorporate traditional APE into their teaching practices effectively. Fourth, the development and utilization of learning themes through traditional APE became more widespread among teachers. Fifth, teachers better understood child development aspects that could be nurtured through traditional APE. Sixth, the training diversified teaching methods through traditional APE, resulting in more engaging and interactive learning experiences was essential. Seventh, teachers' ability to create stimulating learning environments improved. Finally, the training program gave teachers valuable experiences, knowledge, and motivation to enhance their instructional practices. This study highlights the positive outcomes of training PAUD teachers in developing traditional educational game tools, emphasizing the significance of traditional APE in fostering professional competence and enriching early childhood education. Keywords:  Educational Game, Professional Competence Teachers, Traditional Educational Game